Closure at the root of a sharp notch - Churchman, C.M.; Dini, D.; Hills, D.A. (International journal of mechanical sciences, 2006)
Sharp notches subject to remote axial compression suffer closure of the root. In this paper we address this, and determine a first-order approximation to the extent of closure based on the asymptotic solution for a semi-infinite notch. This is then applied to an edge notch, and it is shown that the extent of closure is very small indeed, and likely to be smaller by several orders of magnitude than the notch root radius in any practically realisable case. It also follows that the notch root plasticity present for real materials is likely to encompass this region, and that the ‘open’ notch solution may be used without loss of accuracy.